Molecular Docking Study of Akar Kuning (Arcangelisia flava) Secondary Metabolites as Src Inhibitor - Pratama, Mohammad Rizki Fadhil; Mulyani, Evi; Suratno, Suratno (Indonesian Journal of Cancer Chemoprevention, 2019)
Proto-oncogene tyrosine-protein kinase Src is also known as simply Src is a tyrosine kinase protein which is one of the targets in various cancer therapies such as leukemia. Meanwhile, akar kuning (Arcangelisia flava) has gained significant attention as a medicinal plant that has a cytotoxic effect on various types of cancer cells. This study aims to determine the potential of secondary metabolites of akar kuning as Src inhibitors. Molecular docking was carried out using Autodock Vina 1.1.2 with 2HCK receptors, that quercetin and dasatinib were used as reference ligands. The docking results showed that the highest affinity was shown by berberine with a ΔG value of -9.0 kcal/mol, exceeded quercetin and dasatinib. However, the highest amino acid similarity to quercetin and dasatinib was produced by jatrorrhizine, with 93.33% and 73.91%, respectively. Interestingly, berberine is the ligand with the third-highest similarity after jatrorrhizine and palmatine, while jatrorrhizine has the second-highest affinity after berberine. The results concluded that the combination of berberine and jatrorrhizine is predicted to be optimally used as an Src inhibitor in cancer therapy.